Acute effects of prolonged durations of static stretching on athletic performance and flexibility - Ji, S.; Lu, H.; Sun, Z.; Chen, T.; Li, Z. (Research in Sports Medicine, 2025)
This study aimed to examine the acute effects of prolonged static stretching (SS) versus dynamic stretching (DS), followed by either tennis-specific activation or rest, on physical performance in collegiate tennis players. A randomized crossover trial was conducted with 31 collegiate tennis players. Each participant completed three interventions: (A) SS + activation, (B) DS + activation, and (C) SS + rest. Lower limb muscles were stretching for 3 minutes per group. The activation were tennis footwork drill for 6 minutes. Physical performance was assessed after stretching and after activation using sit-and-reach flexibility, standing long jump (SLJ), agility T-Test, and hand grip strength. Two-way repeated-measures ANOVA was used. Immediately after stretching, SS significantly improved flexibility (sit-and-reach: p < 0.05) but impaired SLJ performance (p < 0.05) and agility (p < 0.05) compared to DS. Crucially, after sport-specific activation exercises, the initial performance declines observed following SS were mitigated, resulting in no significant differences between SS and DS in subsequent SLJ and T-Test performances. Prolonged SS improves flexibility, it temporarily impair agility and explosive performance, however, these drawbacks can be effectively offset through subsequent sport-specific activation exercise.